AICCRA Webinar: Bundled CSA Planning & Prioritization - Mwongera, Caroline; Bonilla Findji, Osana; Huyer, Sophia; Rose, Alison; Kagabo, Desire; Kinyua, Ivy Wambui (Accelerating Impacts of CGIAR Climate Research for Africa, 2021)
The CSA Prioritization seminar was organized by FP2, FP4 and GSI on 10 June 2021, with the aim of highlighting the steps to develop a CSA plan, bundling CSA/CIS, and integrating Gender and Social inclusion in CSA prioritization. The presentation highlighted examples of tools and methodologies that have been developed by the CGIAR and CCAFS for CSA Planning & Prioritization. The seminar also showcased case study examples and resources from previous CGIAR projects on CSA prioritization. Four steps were presented to develop and implement a CSA Plan: 1) situation analysis, 2) targeting and prioritizing, 3) program design, and 4) monitoring and evaluation. The seminar was attended by more than 60 participants from the six AICCRA country teams and partners.